Analisis Springback Pelat ST 37 dengan Tegangan Tarik 343 N/mm2 Tebal 1,98 mm pada Proses V-Bending Dengan Sudut 120, 135, dan 150 serta Arah Tekukan Berlawanan Grain Direction Pelat - Widjaja, Hartono; Khairuman, Rizq Rafi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2025)
Springback is a deviation in the bending angle which tends to return to its original position due to the remaining elasticity of the material in the bending area which crosses the plastic material boundary. The five main parameters that influence springback are punch/die profile, work material, material properties, bending technique, and process conditions. This research focuses on the angle of impact which influences the amount of springback. Tests were carried out with punch angles of 120˚, 135˚, and 150˚ using an AIDA direct servo press machine forming the DSF-C1-A series. The results show that the larger the punch angle, the smaller the springback. All angles produce negative springback values, with the 150° strike angle of -0.990° closest to the target angle. The amount of springback can be calculated using a simple linear regression formula. The angular deviation due to springback can be used as a compensation value in making bending tools to obtain the desired bending results.